THE ROLE OF TRUST AS MEDIATION ON SALESPERSON’S EXPERTISE TO REPURCHASE INTENTION - Oktavia, Riwidya Tri (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2023)
This study focuses on the role of salesperson in increasing repurchase intention. The purpose of this study is to analyze the direct effect of salesperson’s expertise on repurchase intention and its indirect influence through trust. The sample of this study is 140 customers of bank who have received special services from the salesperson and have some minimum deposit selected using probability sampling. The result of this study indicates that salesperson’s expertise has a significant effect on trust and repurchase intention. Trust acts as a partial mediator in the influence of salesperson’s expertise on repurchase intention, bit it acts as a complete mediator in the influence of salesperson’s likeability on repurchase intention.